Event-related brain potentials during the visuomotor mental rotation task: The contingent negative variation scales to angle of rotation. (17th December 2015) - Heath, M.; Hassall, C.D.; MacLean, S.; Krigolson, O.E.
Highlights: We examined the electroencephalographic correlates of the visuomotor rotation task. The amplitude of the contingent negative variation (CNV) was systematically modulated with angle of rotation. The CNV represents the neural processes associated with the cognitive and visuomotor demands of the VMR task. Abstract: Perceptual judgments about the angular disparity of a character from its standard upright (i.e., mental rotation task) result in a concurrent increase in reaction time (RT) and modulation of the amplitude of the P300 event-related brain potential (ERP). It has therefore been proposed that the P300 represents the neural processes associated with a visual rotation. In turn, the visuomotor mental rotation (VMR) task requires reaching to a location that deviates from a target by a predetermined angle. Although the VMR task exhibits a linear increase in RT with increasing oblique angles of rotation, work has not examined whether the task is supported via a visual rotation analogous to its mental rotation task counterpart. This represents a notable issue because seminal work involving non-human primates has ascribed VMR performance to the motor-related rotation of directionally tuned neurons in the primary motor cortex. Here we examined the concurrent behavioral and ERP characteristics of a standard reaching task and VMR tasks of 35°, 70°, and 105° of rotation. Results showed that the P300 amplitude was larger for the standard compared to each VMR task – an effect independent of the angle of rotation. In turn, the amplitude of the contingent negative variation (CNV) – an ERP related to cognitive and visuomotor integration for movement preparation – was systematically modulated with angle of rotation. Thus, we propose that the CNV represents an ERP correlate related to the cognitive and/or visuomotor transformation demands of increasing the angular separation between a stimulus and a movement goal.